Determination of meteoroid physical properties from tristatic radar observations - J. Kero; C. Szasz; A. Pellinen-Wannberg; A. Pellinen-Wannberg; G. Wannberg; A. Westman; D. D. Meisel (Annales Geophysicae, 2008)
In this work we give a review of the meteor head echo observations carried out with the tristatic 930 MHz EISCAT UHF radar system during four 24 h runs between 2002 and 2005 and compare these with earlier observations. A total number of 410 tristatic meteors were observed. We describe a method to determine the position of a compact radar target in the common volume monitored by the three receivers and demonstrate its applicability for meteor studies. The inferred positions of the meteor targets have been utilized to estimate their velocities, decelerations and directions of arrival as well as their radar cross sections with unprecedented accuracy. The velocity distribution of the meteoroids is bimodal with peaks at 35–40 km/s and 55–60 km/s, and ranges from 19–70 km/s. The estimated masses are between 10−9–10−5.5 kg. There are very few detections below 30 km/s. The observations are clearly biased to high-velocity meteoroids, but not so biased against slow meteoroids as has been presumed from previous tristatic measurements. Finally, we discuss how the radial deceleration observed with a monostatic radar depends on the meteoroid velocity and the angle between the trajectory and the beam. The finite beamwidth leads to underestimated meteoroid masses if radial velocity and deceleration of meteoroids approaching the radar are used as estimates of the true quantities in a momentum equation of motion.